INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN TEACHING THE SUBJECT OF TECHNOLOGY - Khanifa Berdieva (Bright Mind Publishing, 2025)
This article explores the significance of applying innovative pedagogical technologies in teaching the subject of Technology. Modern teaching methods, information and communication technologies, interactive approaches, project-based learning, and STEAM education are analyzed for their role in developing students’ practical skills, creative thinking, and critical thinking abilities. The study emphasizes that the use of innovative pedagogical technologies is a key factor in improving the quality of education.
Keywords: Technology education, innovative pedagogical technologies, interactive methods, ICT, project-based learning, STEAM education